PENERAPAN KONSEP VALUE FOR MONEY PADA PENGELOLAAN KEUANGAN DAERAH DALAM MEWUJUDKAN GOOD GOVERNMENT GOVERNANCE (TATA KELOLA PEMERINTAHAN YANG BAIK) PADA KABUPATEN MUSI BANYUASIN - Septariani, Jumania (Universitas Muhammadiyah Palembang, 2017)
ABSTRACT This study aimed to determine the implementation of the concept of value for money in the management of regional finances in realizing Good Government Governance (Good Governance) in Musi Banyuasin Regency. The research method was qualitative methods. Qualitative method in this research was, the author conducted an analysis of data in the form of information, collecting tangible data figures calculation results statistically, general description of the object of research, applying the concept of value for money in Musi Banyuasin Regency that had been economical, efficient and effective. The results of this study indicated that the economic ratio was already economical as this was marked by the amount of revenue realization had exceeded the revenue budget due to increased PAD and balancing funds received from the center. In efficient efficiency ratios this was marked by the small cost to levy local taxes. Meanwhile, the effectiveness ratio had been effective because the revenue target had been reached. Good Government Governance can be realized in Musi Banyuasin Regency if viewed based on the calculation with the concept of value for money, because it had been economical, efficient and effective. The concept of value for money is only one of the principles of Good Government Governance (Good Governance). Other principles, namely; participation, accountability, transparency, responsiveness, justice, community-oriented, forward-looking and law enforcement can be determined to the implemention Good Governance